Front Cover: Flavonoid‐Derived Human Phenyl‐γ‐Valerolactone Metabolites Selectively Detoxify Amyloid‐β Oligomers and Prevent Memory Impairment in a Mouse Model of Alzheimer's Disease. Issue 5 (4th March 2020) - Ruotolo, Roberta; Minato, Ilaria; La Vitola, Pietro; Artioli, Luisa; Curti, Claudio; Franceschi, Valentina; Brindani, Nicoletta; Amidani, Davide; Colombo, Laura; Salmona, Mario; Forloni, Gianluigi; Donofrio, Gaetano; et al.
Abstract : Mol. Nutr. Food Res . 2020, 64, 1900890 DOI: 10.1002/mnfr.201900890 Amyloid β ‐oligomers are the most proximal neurotoxic species in Alzheimer's disease. Multiple phenyl‐ γ ‐valerolactones, the major group of circulating flavan‐3‐ol metabolites in humans, selectively relieve oligomer‐induced cytotoxicity and actively remodel preformed oligomers into non‐toxic amorphous aggregates. In article 1900890, Simone Ottonello and co‐workers discover that treatment of A β ‐oligomers with the 5‐(4′‐hydroxyphenyl)‐ γ ‐valerolactone metabolite prior to brain injection strongly reduces memory deterioration and neuroinflammation in a mouse model of A β ‐oligomers‐induced memory impairment.